The effect of problem-based learning model assisted by Google Site on the students’ mathematical concept understanding ability - Anida Nurul Fadilah; S. Sutirna; H. Haerudin (Universitas Sarjanawiyata Tamansiswa, 2023)
The study aims to determine the effect of the problem-based learning (PBL) model assisted by Google Site on the students’ mathematical concept understanding ability. This type of research uses quantitative research with an experimental method. The subject is two classes, 30 students in VIII G as the experimental class and 30 students in VIII I as the control class. The data collection technique uses a description test in the materials in flat-sided shape and interviews for observation. Technique data analysis using the t-test with SPSS version 26 and determining the magnitude of the effect using the effect size test. The result obtained that the average mathematical concept understanding ability of students who receive learning with the PBL model assisted by Google Site is better than students who receive learning with conventional learning. Thus, it can be shown that a significant effect of applying the PBL model assisted by Google Site on the mathematical concept understanding ability. The effect size on the students’ post-test is 1.85. This shows that the effect of the problem-based learning model assisted by Google Site on the students’ mathematical concept understanding ability is in the high category.